PEDAGOGICAL OPPORTUNITIES FOR THE EDUCATION OF PHYSICAL QUALITIES IN PRESCHOOL CHILDREN - Achilova Saxibakhon Khamidovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the use of moving games as a means of physical education in the upbringing of physical qualities through the application of moving images in preschool children and on this basis to determine the theoretical basis and methodological ways of technology of development of children's movement activities in the conditions of preschool institutions, in the process of achieving the goal, it is envisaged to organize and conduct research on physical education and mass health activities carried out for the development of children's mobility activities in the conditions of pre-school educational institutions.